Application of the de Job method in the evaluation of the stoichiometry of uranyl phosphate complexes sorbed on bentonite - Grabias, Ewelina; Gładysz-Płaska, Agnieszka; Lipke, Agnieszka; Pikus, Stanisław; Majdan, Marek (European Journal of Chemistry, 2016)
For the first time, the continuous variation method was applied for the evaluation of the stoichiometry of uranyl phosphate complexes sorbed on bentonite. Sorption of UO2(CH3COO)2⋅2H2O in the presence of Na2HPO4⋅7H2O from 0.001 mol/L solutions led to the appearance of maxima in the sorption peaks of U(VI) and P(V) ions at molar ratios of [U(VI)]/[P(V)]s = 1.4, 3.3, 3.6 and 1.2, 1.7. It is suggested, based on complementary XRD and XPS data, that the UO2HPO4 complex is located on aluminols (ºAl-OH) whereas the (UO2)3(PO4)2⋅4H2O complex is precipitated in the interlamellar space of bentonite. The participation of (UO2)3(OH)5+ and (UO2)4(OH)7+ species in the formation of U(VI) surface complexes is suggested, based on the deconvolution of sorption spectra of U(VI) on the bentonite in the presence of phosphates.